Happy Birthday Mirjana ! - Pilipović, Stevan (Sarajevo Journal of Mathematics, 2024)
This issue of Sarajevo Journal of Mathematics is devoted to our editor in chief Acad. Prof. Dr. Mirjana Vuković on the occasion of her jubilee. Here we will give a brief overview of her life and work.